Uji Efektivitas Antibakteri Ekstrak Etanol Pakkat (Callamus Caesius Blume) dan Ekstrak Jeruk Nipis (Citrus Aurantifolia) terhadap Bakteri Escherichia Coli ATCC 25922 - Monica, Veny; Lubis, Yolanda Eliza Putri; Mutia, Maya Sari (Journal of Telenursing (JOTING), 2024)
The purpose of this study was to determine the comparison of the antibacterial effectiveness test of packet extract (calamus caesius Blume) with lime extract (citrus aurantifolia) against Escherichia coli ATCC 25922 bacteria—experimental research method with in vitro design. The results showed that the inhibition zone in lime extract with the highest average value at a concentration of 100% was 9.23 mm in the moderate category. Still, it was not effective as an antibacterial because it had not entered the category of strong or very strong inhibition zones. The conclusion is that there is no inhibition zone of pakkat extract against the growth of Escherichia coli ATCC 25922 bacteria (p>0.05) and there is an inhibition zone of lime extract but it is not significant against the growth of Escherichia coli ATCC 25922 bacteria (p>0.05). Keywords: Pakkat Extract, Lime Extract, Bacteria Escherichia Coli Bacter